An end to Nordic exceptionalism? Europeanisation and Nordic development policies. Issue 1 (2nd January 2016) - Elgström, Ole; Delputte, Sarah
ABSTRACT: The Nordic countries have traditionally been praised for their generous and advanced development policies. Recently, however, it has been claimed that the Nordic model has faded: that the Nordic donors have become more similar to other European donors. One possible reason for such trends is influences from EU policies, that is, Europeanisation. This article critically evaluates such claims by presenting arguments for and against Europeanisation effects. We argue that changes have indeed taken place. The Nordic exceptionalism has been eroded. At the same time, a convergence of European aid policies has occurred. The question is if this is the consequence of Europeanisation – or is it rather a result of Nordicisation (the Nordic countries influencing the EU), or perhaps like-mindisation (a broader set of progressive member states having impact upon EU policies)? We suggest that Europeanisation has been extremely weak while there is strong evidence of Nordicisation but also, and increasingly, of like-mindisation. Today, a core group of mainly northern member states, including the Nordics, are the main driving forces behind European aid convergence.